Drying banana seeds for ex situ conservation - Kallow, Simon; Garcia Zuluaga, Manuela; Fanega Sleziak, Natalia; Nugraha, Bayu; Mertens, Arne; Janssens, Steven B.; Gueco, Lavernee; Valle-Descalsota, Michelle Lyka; Vu, Tuong Dang; Vu, Dang Toan; Li, Loan Thi; Vandelook, Filip; et al. (Oxford University Press, 2022)
The ability of seeds to withstand drying is fundamental to ex situ seed conservation but drying responses are not well known for most wild species including crop wild relatives. We look at drying responses of seeds of Musa acuminata and Musa balbisiana, the two primary wild relatives of bananas and plantains, using the following four experimental approaches: (i)We equilibrated seeds to a range of relative humidity (RH) levels using non-saturated lithium chloride solutions and subsequently measured moisture content (MC) and viability. At each humidity levelwe tested viability using embryo rescue (ER), tetrazolium chloride staining and germination in an incubator.We found that seed viabilitywas not reduced when seedswere dried to 4% equilibrium relative humidity (eRH; equating to 2.5% MC). (ii)We assessed viability ofmature and less mature seeds using ER and germination in the soil and tested responses to drying. Findings showed that seeds must be fully mature to germinate and immature seeds had negligible viability. (iii) We dried seeds extracted from ripe/unripe fruit to 35–40% eRH at different rates and tested viability with germination tests in the soil. Seeds from unripe fruit lost viability when dried and especially when dried faster; seeds from ripe fruit only lost viability when fast dried. (iv) Finally, we dried and re-imbibed mature and less mature seeds and measured embryo shrinkage and volume change using X-ray computer tomography. Embryos of less mature seeds shrank significantly when dried to 15% eRH from 0.468 to 0.262 mm3, but embryos of mature seeds did not.